ANALISIS PERBANDINGAN KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, PROFITABILITAS, DAN SOLVABILITAS PADA PT BUMI SERPONG DAMAI TBK DAN PT SUMMARECON AGUNG TBK PERIODE 2015–2024 - Nurjumratunnisa, Nurjumratunnisa; Puji Muniarty (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the comparative financial performance of PT Bumi Serpong Damai Tbk and PT Summarecon Agung Tbk based on liquidity, profitability, and solvency ratios during the period 2015–2024. This research employs a quantitative comparative approach using secondary data in the form of audited annual financial statements. The analysis includes Current Ratio (CR), Return on Assets (ROA), and Debt to Asset Ratio (DAR), which are tested using normality, homogeneity, and Independent Sample t-test with the assistance of SPSS. The results indicate that there are significant differences in CR and DAR, while no significant difference is found in ROA. These findings suggest that both companies differ in liquidity management and capital structure, but have relatively similar capabilities in generating profits.